Pengaruh Strategi Branding Image dalam Pemasaran Pendidikan Terhadap Peningkatan Daya Saing Madrasah - Sakinah, Syifa Sari; Nurmila, Nina; Kasmin (AKSI: Jurnal Manajemen Pendidikan Islam, 2024)
The competition among educational institutions is becoming increasingly intense, prompting schools to enhance their quality. One of the crucial elements in competitiveness is the branding image of the school. Consequently, the management of institutions is required to continuously improve their capabilities to compete. The aim of this study is to determine the extent to which branding image strategies in educational marketing impact the competitiveness of madrasahs. Based on statistical analysis results: The branding image strategy at MAN 2 Bandung received an average score of 3.06, categorized as adequate. Educational marketing at MAN 2 Bandung also received an average score of 3.06, categorized as adequate. Competitiveness at MAN 2 Bandung received an average score of 4.32, categorized as very high. Overall results indicate that branding image strategies in educational marketing have a positive and significant impact on enhancing the competitiveness of the madrasah at MAN 2 Bandung, with a significance value for X1 and X2 against Y being (0.00 < 0.05) and a t-statistic value of 804.409 > t-table 1.025. Therefore, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, with an R Square value of 0.381. This means that variables X1 and X2 have a significant effect on variable Y by 38%, while the remaining 62% is explained by other variables such as the quality of facilities and infrastructure, staff performance, and so on. Thus, as the branding image strategy and educational marketing improve, the competitiveness of the madrasah also improves. It is recommended that MAN 2 Bandung pay more attention to these two aspects to maintain their competitive advantage.